2002
DOI: 10.1144/gsl.sp.2002.201.01.07
|View full text |Cite
|
Sign up to set email alerts
|

The 40 Ar/ 39 Ar ages from the West Sudetes (NE Bohemian Massif): constraints on the Variscan polyphase tectonothermal development

Abstract: The West Sudetes (NE margin of the Bohemian Massif) consist of a complex mosaic of several tectonometamorphic units juxtaposed during the Variscan orogeny. The polyphase Variscan tectonothermal development of the West Sudetes was determined by 4~ ages of single grains and mineral concentrates. Late Famennian (359 Ma) mica ages from the high-grade G6ry Sowie Block suggest continuous uplift after a Late Devonian high temperature-low pressure (HT-LP) event contemporaneous with the end of subduction-related high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 49 publications
2
54
0
Order By: Relevance
“…The lat ter con clu sion pre sum ably also ex tends to other iso tope sys tems stud ied in the OSD rocks. The Rb-Sr phengite and bi o tite ages for gneiss es of the two for ma tions range be tween 335 Ma and ~319 Ma (Borkowska et al, 1990;Lange et al, 2005) and are well com pat i ble with the Ar-Ar ages de ter mined be tween 341 Ma and 320 Ma (Maluski et al, 1995;Marheine et al, 2002;Glascock et al, 2003;Schnei der et al, 2006). These are cool ing ages, yet of ten consid ered to re flect the tim ing of Variscan meta mor phism in the gneiss es.…”
Section: Previous Isotopic Age Data For Gneisses With Basic Referencementioning
confidence: 73%
See 1 more Smart Citation
“…The lat ter con clu sion pre sum ably also ex tends to other iso tope sys tems stud ied in the OSD rocks. The Rb-Sr phengite and bi o tite ages for gneiss es of the two for ma tions range be tween 335 Ma and ~319 Ma (Borkowska et al, 1990;Lange et al, 2005) and are well com pat i ble with the Ar-Ar ages de ter mined be tween 341 Ma and 320 Ma (Maluski et al, 1995;Marheine et al, 2002;Glascock et al, 2003;Schnei der et al, 2006). These are cool ing ages, yet of ten consid ered to re flect the tim ing of Variscan meta mor phism in the gneiss es.…”
Section: Previous Isotopic Age Data For Gneisses With Basic Referencementioning
confidence: 73%
“…Later geo chem i cal and geo chron ol ogi cal data fur nished the base for a hy poth e sis that all gneiss es in the dome came from a sin gle ~500 Ma gra nitic protolith. The orig inal gran ites were to be come sub stan tially trans formed and even tu ally di ver si fied dur ing Variscan de for ma tion and migmatisation be tween 360 Ma and 340 Ma, then cooled at 340-330 Ma (Maluski et al, 1995;Turniak et al, 2000;Lange et al, 2002Lange et al, , 2005Gordon et al, 2005;Bröcker et al, 2009Bröcker et al, , 2010Štípská et al, 2012) and zon ally sheared at ~321 Ma (Marheine et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…According to these authors the age of the granite intrusion is 480-450 Ma. Zircon dating by U-Pb and Pb-Pb methods slightly moved the age limits and fixed the crystallization of the Izera granite at 514-480 Ma as mentioned above (Korytowski et al, 1993;Oliver et al, 1993;Kröner et al, 1994;Philippe et al, 1995;Marheine et al, 2002). According to Żelaźniewicz et al (2003) dating of zircons from the intraschists gneisses from Gierczyn has shown that their granite protolith intruded into the envelope at 505 Ma, the Świeradów gneisses (diatextites) were partially melted between 513-483 Ma, while leucogranites from Kotlina crystallized/intruded in the interval of 508-483 Ma.…”
Section: Geochronologymentioning
confidence: 99%
“…For the Karkonosze granite they were reported to average at 304 Ma and 290 Ma (K-Ar and Rb-Sr, respectively) that is somehow controversial taking into account the closure temperature of the Rb-Sr system higher than that of the K-Ar system. According to 40 Ar/ 39 Ar determinations of Marheine et al (2002), the shearing activity within the Krknoše-Jizera terrane dated at about 325-320 Ma was accompanied by comtemporary pluton emplacement (Pin et al, 1987;Mierzejewski et al, 1994). The upper limit of the tectonometamorphic and magmatic activity has been estimated at 314-312 Ma ( 40 Ar/ 39 Ar) − the Namurian/Westphalian boundary (Manheine et al, 2002).…”
Section: Geochronologymentioning
confidence: 99%
See 1 more Smart Citation